Education and the poverty trap in rural china: Closing the trap. - Knight, J; Shi, L; Quheng, D (Taylor and Francis, 2010)
This is an ambitious attempt to view the relationships involving education and income as forming a system, and one that can generate a poverty trap. The setting is rural China, and the data are from a national household survey for 2002, designed with research hypotheses in mind. The paper shows how and why the returns to education vary according to household and community income. It examines the effects of education on income, innovation, health and happiness, and shows how education can be important in helping people to escape from various dimensions of poverty. The results are brought together to form an empirical model of a poverty trap, and the implications for poverty analysis and for educational policy are considered.